2018
DOI: 10.1016/j.athoracsur.2018.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve for Robot-Assisted Minimally Invasive Thoracoscopic Esophagectomy: Results From 312 Cases

Abstract: The learning phase of thoracic laparoscopic RAMIE consisted of 70 procedures in 55 months. A structured proctoring for RAMIE substantially reduced the number of procedures and time required to achieve proficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 24 publications
3
77
0
1
Order By: Relevance
“…Furthermore, it was reported that RAMIE can safely be performed with the patient in semiprone position (26), which can reduce the incidence of postoperative pulmonary complications (27). The duration of the learning curve for RAMIE has been reported to take 20-70 cases (28)(29)(30). One study found that the use of a structured training pathway that involved proctoring reduced the learning curve for RAMIE from 70 to 24 cases (30).…”
Section: Ramie Vs Open Esophagectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was reported that RAMIE can safely be performed with the patient in semiprone position (26), which can reduce the incidence of postoperative pulmonary complications (27). The duration of the learning curve for RAMIE has been reported to take 20-70 cases (28)(29)(30). One study found that the use of a structured training pathway that involved proctoring reduced the learning curve for RAMIE from 70 to 24 cases (30).…”
Section: Ramie Vs Open Esophagectomymentioning
confidence: 99%
“…The duration of the learning curve for RAMIE has been reported to take 20-70 cases (28)(29)(30). One study found that the use of a structured training pathway that involved proctoring reduced the learning curve for RAMIE from 70 to 24 cases (30). In light of the increasing centralization of care, this seems to be a feasible number of cases in order to complete the learning curve within an acceptable time frame.…”
Section: Ramie Vs Open Esophagectomymentioning
confidence: 99%
“…It was considered that the CAS-LCWHTOs were performed with greater CAS experience obviously after completion of the learning curve for CAS compared with the cases performed before the learning curve completion. Because the learning curve for CAS-LCWHTO is not well defined, we referred to the previously reported learning curve for CAS in various fields; the learning curves for CAS were completed in 20-70 cases [16,17]. In the present study, it was determined that 70 cases would be required to complete the learning curve for CAS-LCWHTO.…”
Section: Patientsmentioning
confidence: 99%
“…This means that a substantial part of the included patients in the RAMIE group underwent surgery during the learning phase, as a previous study indicates that the learning curve for RAMIE takes up to 70 cases to complete. 19 Intraoperative blood loss and operating time are known to decrease with increasing experience, which might imply that the reported longer duration of surgery in the RAMIE group might not be present anymore and that even less intraoperative blood loss might be observed after completion of the learning curve. However, to adequately investigate such outcomes, studies on larger case series of patients who undergo RAMIE after completion of the surgeon's learning curve are warranted.…”
mentioning
confidence: 98%
“…A recent study reported that the learning curve of RAMIE can be decreased from 70 to 24 cases when adhering to a structured training pathway, which successively involves a robotic cadaver course, case observations, and proctoring by an experienced peer. 19 By shortening the learning curve of RAMIE, structured training pathways likely increase the safety and efficacy of the implementation phase. The facilitation and promotion of such structured training pathways in one of the key aims of the 'Upper GI International Robotic Association (UGIRA)', which was established in 2017 and serves as an important platform to connect surgeons who are willing to implement RAMIE (and other robot-assisted esophagogastric techniques) to proctors worldwide.…”
mentioning
confidence: 99%